Embeddedness: a framework for understanding China-Nordics Relations - Reza Rahmati (رهیافتهای سیاسی و بین المللی)
In the late two decades of the 21th century, China-Nordic relations experienced a new atmosphere, and the complexity of this relationship increased. China is growing economically, and the Nordics have needed Chinese investment to develop their combined welfare state model. However, China's willingness to use the economic-political capacity of the Nordic region, in addition to facing external challenges, has also been explained by the state of social variables. The main question of the present study is how the mechanisms of China-Nordic economic actions are engraved within the social context? In answer to this question, the present study has tried to explain the China-Nordic economic action in the context of sovereignty by adhering to the tradition of economic sociology. Historical rationality refers to the state of adherence of structural and historical patterns, the history of relations, and historical considerations to economic relations. Cognitive-psychological wisdom implies the attachment of mental perceptions, mutual cognitive elements, the image of society and the perception of citizens / elites to economic relations. Political governance also implies the attachment of political priorities, political decisions, the political position of the country, the position of national and vital interests, the balance of power and international variables to economic arrangements. The present study is fundamental in terms of purpose and seeks to explain the framework of Sino-Nordic relations in the context of economic sociology.